2006
DOI: 10.1074/jbc.m512559200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Albumin Endocytosis by PSD95/Dlg/ZO-1 (PDZ) Scaffolds

Abstract: The constitutive reuptake of albumin from the glomerular filtrate by receptor-mediated endocytosis is a key function of the renal proximal tubules. Both the Cl ؊ channel ClC-5 and the Na ؉ -H ؉ exchanger isoform 3 are critical components of the macromolecular endocytic complex that is required for albumin uptake, and therefore the cell-surface levels of these proteins may limit albumin endocytosis. This study was undertaken to investigate the potential roles of the epithelial PDZ scaffolds, Na ؉ -H ؉ exchange … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 57 publications
0
41
0
Order By: Relevance
“…This tethering also reduces the lateral mobility in the cell membrane of these proteins by anchoring the complex to the underlying actin cytoskeleton via accessory proteins such as ezrin, which is highly expressed in gastric epithelia (51). It has already been shown that NHERF-2 is important for the trafficking of membrane transporters such as NHE3 (47) and ion channels such as ClC-5 and TRPV5 (39,52). We have recently also shown that NHERF-1 and NHERF-2 differentially regulate albumin uptake in renal proximal tubule cells by mechanisms that involve altering the cell-surface levels of ClC-5 in different domains of the apical membrane (39).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…This tethering also reduces the lateral mobility in the cell membrane of these proteins by anchoring the complex to the underlying actin cytoskeleton via accessory proteins such as ezrin, which is highly expressed in gastric epithelia (51). It has already been shown that NHERF-2 is important for the trafficking of membrane transporters such as NHE3 (47) and ion channels such as ClC-5 and TRPV5 (39,52). We have recently also shown that NHERF-1 and NHERF-2 differentially regulate albumin uptake in renal proximal tubule cells by mechanisms that involve altering the cell-surface levels of ClC-5 in different domains of the apical membrane (39).…”
Section: Discussionmentioning
confidence: 91%
“…For the experiments to silence NHERF-2, HT-29 cells were transfected with plasmids encoding siRNA directed against two different regions of NHERF-2 (Shag-274 and Shag-361) or control (Shag-FF). These plasmids have been shown previously to effectively suppress the endogenous levels of NHERF-2 (38,39). All experiments were performed 48-h post-transfection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased receptor internalization could simply increase the speed of receptor trafficking, resulting in earlier degradation and localization in the lysosome. Furthermore, many published reports demonstrate that PDZ ligand-PDZ domain containing protein interactions facilitate plasma membrane localization (40,41,61,62). Interruption of this interaction has been shown to allow faster internalization of ligand-stimulated receptor (40,61).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that knockdown of specific PDZ domain containing proteins results in increased internalization of receptors subsequent to ligand stimulation (40,41). Because an increased rate of internalization of the CXCR2 352T mutant could explain the increased degradation and earlier lysosome co-localization as compared FIGURE 1.…”
Section: Cooh-terminal Pdz Ligand Deletion Has No Effect On Either Rementioning
confidence: 99%